KAJIAN PERUBAHAN STATUS KELURAHAN MENJADI DESA DI KABUPATEN TAKALAR STUDY OF CHANGE STATUS URBAN VILLAGE TO VILLAGE IN TAKALAR REGENCY - Umar Nain (Jurnal Pallangga Praja (JPP), 2020)
Regional autonomy gives authority to the regions to regulate their household affairs in accordance with the potential of the region. The purpose of this study was to determine the problems of the urban village based on the condition of the underdeveloped community into urban areas; analyze changes in urban village into Villages based on various regulations on villages; analyze the stages of the process and various requirements 60 60 that must be met in making changes to the status of the urban village to village. The approach used in this research is through literature studies and regulatory studies. To strengthen both studies are supported by field data conducted through observation and interviews. The informants in this study are the head of urban village and his apparatus, community leaders, religious leaders, youth leaders and social groups and members of the Community Empowerment Institution in the urban village. Data analysis through 3 stages, namely data reduction, data presentation, and verification and conclusions. The results showed that the Rajaya urban village, Parangluara urban village, Takalar urban village and Bontolebang urban village were sufficiently fulfilling the requirements, rational and worthy of changing the status from urban village to village